Fetal diagnosis of testicular torsion: what shall we tell the parents?. (2nd November 2014) - Melcer, Y.; Mendlovic, S.; Klin, B.; Keidar, R.; Lysyy, O.; Herman, A.; Maymon, R.
Abstract Objectives The objectives of this study are to present our collective experience with the prenatal diagnosis of testicular torsion and to propose a possible prenatal management scheme. Methods We retrospectively collected and reviewed all medical records of cases that were diagnosed with perinatal testicular torsion in our medical center between the years 2002 and 2013. Prenatal torsion was categorized as torsion diagnosed in utero or on immediate newborn examination. Results A total of five unilateral prenatal torsions were diagnosed. Two fetuses were diagnosed in the third trimester of pregnancy. In both cases, cesarean section was performed immediately upon diagnosis. One newborn underwent immediate orchiectomy with contralateral orchiopexy. Torsion was confirmed by pathological examination. The other was managed conservatively, just as the three newborns who were diagnosed immediately after birth. On follow‐up scan, the affected testicle was found atrophied with lack of blood flow on color Doppler examination. The unaffected contralateral testicle remained within the normal size with good blood flow. Conclusions Prenatal diagnosis of unilateral testicular torsion is a coincidental rare finding. Because the twisted testicle cannot be salvaged, induced delivery and prompt surgery are not recommended. © 2014 John Wiley & Sons, Ltd.